Dynamic strain aging of Al0.3CoCrFeNi high entropy alloy single crystals. (November 2015) - Yasuda, Hiroyuki Y.; Shigeno, Kyosuke; Nagase, Takeshi
Graphical abstract: Abstract: Single crystals of Al0.3 CoCrFeNi high entropy alloy were prepared by the floating zone method and the deformation behavior was examined. Dynamic strain aging accompanied by a serrated flow was found to occur in the single crystals at 873 K and 1073 K. Al atoms in the alloy played an important role in the dynamic strain aging. Distinct planar slip on (1 1 1) plane was also observed in Al0.3 CoCrFeNi single crystals.